Pathologic complete response after induction therapy-the role of surgery in stage IIIA/B locally advanced non-small cell lung cancer - Schreiner, Waldemar; Gavrychenkova, Sofiia; Dudek, Wojciech; Rieker, Ralf; Lettmaier, Sebastian; Fietkau, Rainer; Sirbu, Horia (Journal of Thoracic Disease, 2018)
Background: Pathologic complete response (pCR) is dominant prognostic factor determining favorable outcome in locally advanced non-small cell lung cancer (NSCLC) after induction therapy (IT). There is no non-operative diagnostics that adequately estimates the pCR. Aim of this retrospective study was to assess the correlation between clinical and pathological factors in patients with pCR. Methods: Twenty-five patients with pCR after curative lung resection following IT were assessed using univariate and multivariate Cox regression and descriptive analysis. The survival rate was estimated by Kaplan-Meier method. Results: The IT included chemoradiation with median doses of 50.4 Gy (range, 45-59.4 Gy) combined with platinum-based chemotherapy in 23 patients (92%) and induction platinum-based chemotherapy in 2 patients (8%). Clinical tumor stage before IT was IIIA in 21, IIIB in 4 patients. Mean interval between IT and surgery was 8.1±3.0 weeks. Perioperative morbidity and 30-day mortality was 32% and 4%, respectively. There was no significant correlation of pCR and different clinical and pathological factors. The estimated 5-year long-term survival (LTS) and progressive-free survival (PFS) was 57% and 54%, respectively. The median LTS and PFS was not reached. Conclusions: pCR in patients with locally advanced NSCLC following IT is an independent prognostic factor, without correlation with pathological and clinical factors. Non-operative accurate assessment of pCR is currently impossible. Surgical resection enables secure identification of pCR and might improve the patient stratification for additive therapy.
EVALuna2:35733